Quality of Life in Patients with Atrial Fibrillation Undergoing Pulmonary Vein Isolation: Short-Term Follow-Up Study - Matiss Linde; Kristine Jubele; Kaspars Kupics; Anastasija Nikitina; Andrejs Erglis (Medicina)
Background and Objectives: Atrial fibrillation (AF) significantly impacts the quality of life (QoL) of affected individuals. Pulmonary vein isolation (PVI) has emerged as a therapeutic approach to manage AF and improve QoL. This study aimed to assess the QoL in patients with AF undergoing PVI. Methods and Materials: A total of 97 AF patients undergoing PVI (radiofrequency 52.6% (n = 51) and cryoablation 47.4% (n = 46)) at Pauls Stradins Clinical University Hospital were included in this study. QoL was measured using the 36-Item Short-Form Survey (SF-36) before PVI and during a follow-up period of 5.98 ± 1.97 months. Results: This study consisted of 60.8% (n = 59) males, with a mean age of 60.06 ± 11.61 years. A total of 67.0% (n = 65) of patients had paroxysmal AF, and 33.0% (n = 32) had persistent AF. The SF-36 questionnaire revealed major improvements across multiple QoL domains post-PVI, reaching a statistical significance of p < 0.01. Patient factors, such as female gender ([estimate 21.26, 95% CI (7.18, 35.35)], p < 0.01), persistent AF ([estimate 15.49, 95% CI (2.83, 28.15)], p = 0.02), and restored sinus rhythm ([estimate 14.35, 95% CI (1.65, 27.06)], p = 0.03), were associated with significantly improved QoL. Conclusions: PVI in patients with AF positively influences various dimensions of QoL, as evidenced by significant improvement across multiple SF-36 domains. These findings emphasize worsened QoL in patients with AF and the potential benefits of PVI enhancing the overall wellbeing of individuals with AF.